2013
DOI: 10.1051/0004-6361/201322098
|View full text |Cite
|
Sign up to set email alerts
|

Extremely metal-poor galaxies: The H i content

Abstract: Context. Extremely metal-poor (XMP) galaxies are chemically, and possibly dynamically, primordial objects in the local Universe.Aims. Our objective is to characterize the H i content of the XMP galaxies as a class, using as a reference the list of 140 known local XMPs compiled by Morales-Luis et al. (2011). Methods. We have observed 29 XMPs, which had not been observed before at 21 cm, using the Effelsberg radio telescope. This information was complemented with H i data published in literature for a further 53… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
100
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 55 publications
(114 citation statements)
references
References 123 publications
14
100
0
Order By: Relevance
“…XBCDs are found to fall off the mass/luminosity -metallicity relation compiled from literature data in Filho et al (2013), which is consistent with the presence of chemically unpolluted gas in these systems. It is worth remarking in this context that Sánchez almeida et al (2014) studied, using long-slit spectroscopy, the oxygen abundance along the major axis of seven SF galaxies, including HS 2236+1344.…”
Section: Region 1 Region 2 Region 3 F(λ)/f(hβ) I(λ)/i(hβ) F(λ)/f(hβ) supporting
confidence: 79%
See 1 more Smart Citation
“…XBCDs are found to fall off the mass/luminosity -metallicity relation compiled from literature data in Filho et al (2013), which is consistent with the presence of chemically unpolluted gas in these systems. It is worth remarking in this context that Sánchez almeida et al (2014) studied, using long-slit spectroscopy, the oxygen abundance along the major axis of seven SF galaxies, including HS 2236+1344.…”
Section: Region 1 Region 2 Region 3 F(λ)/f(hβ) I(λ)/i(hβ) F(λ)/f(hβ) supporting
confidence: 79%
“…A&A 569, A110 (2014) These systems are very scarce in the nearby Universe (Izotov & Thuan 2007;Kniazev et al 2004;Papaderos et al 2008;Guseva et al 2009; see also Skillman 2012) with only about 100 of them currently known (see Morales-Luis et al 2011;Filho et al 2013, for recent compilations of literature data). The most metalpoor ones are SBS 0335-052 W (12 + log(O/H) 6.9 .…”
Section: Introductionmentioning
confidence: 99%
“…These galaxies have a number of properties consistent with disks being assembled by accretion of gas (Elmegreen et al 2012b;Sánchez Almeida et al 2013. In particular, they are enshrouded by large amounts of neutral gas, so that M g /M is typically as large as 20 (Filho et al 2013). The ratio is so large that normal stellar evolution cannot produce enough metals for their HI gas to have the same metallicity as that observed in the HII regions of the galaxies, which are already extremely metal poor because XMP galaxies are selected to have Z < 0.1 Z .…”
Section: Neutral Gas Observationsmentioning
confidence: 94%
“…In a systematic search for XMP galaxies in SDSS-DR7, Morales-Luis et al (2011) find that 75 % of them have either cometary shape or are formed by chained knots. Likewise, from the comprehensive catalog of 140 known XMPs used by Filho et al (2013), 80 % have cometary structure or two or multiple star-forming regions. For reference, only 0.2 % of the star-forming galaxies in the Kiso survey are cometary (Elmegreen et al 2012b).…”
Section: Accretion Inferred From Stellar Observationsmentioning
confidence: 99%
“…Although there might be an inevitable overlap between them (e.g., some clumpy/chain or cometary/tadpole EELGs may be also interpreted in terms of interactions) a more detailed description of both the distribution of the star-forming regions and the shape of the underlying diffuse component in broadband images remains interesting. In particular, it may be useful to study the possible mechanisms responsible for the origin of the starburst and chemical enrichment in these galaxies (e.g., Papaderos et al 2008;Filho et al 2013;Sánchez Almeida et al 2013, 2014Amorín et al 2009) and to compare them with galaxies of similar morphologies identified at higher redshifts (e.g., Elmegreen et al 2012Elmegreen et al , 2013Amorín et al 2012b). …”
Section: Visual Classificationmentioning
confidence: 99%